Pre-clinical studies comparing the anti-inflammatory potential of artemisinic compounds by targeting NFκB/TNF-α/NLRP3 and Nrf2/TRX pathways in Balb/C mice - Kazmi, Syeda Tayyaba Batool; Fatima, Humaira; Naz, Iffat; Kanwal, Nosheen; Haq, Ihsan-ul (Frontiers in Pharmacology, 2024)
Artemisinin, artemether, artesunate, and dihydroartemisinin are renowned for their antimalarial potential. The current study aims to repurpose the above-mentioned artemisinic compounds (ACs) by conducting an intercomparison to evaluate their antiinflammatory potential (AIP). Oral administration of ACs to BALB/c mice (50 and 100 mg/kg BW) significantly alleviated the carbon tetrachloride (1ml/kg body weight (BW)) induced inflammation in comparison with silymarin. Reduced levels of several inflammatory markers including nitric oxide, thiobarbituric acid reactive substances, interleukin-1 beta, nuclear factor kappa B, tumor necrosis factor alpha, and nucleotide-binding oligomerization domain-like receptor protein 3, underscore the substantial AIP of ACs. Immunohistochemical analysis depicted the revitalized percent relative expression of antioxidant markers i.e., nuclear factor erythroid-2-related factor and thioredoxin in groups treated with ACs. Behavioral analysis revealed that ACs-treated groups significantly (p<0.05) attenuated the memory deficit, anxiety, and depressive-like behavior. Moreover, histopathological, hematological, serological, and endogenous antioxidant profiles indicated substantial AIP of ACs. Findings of comet assay further bolstered the compelling evidence as DNA damage was significantly (p<0.05) curbed down after ACs (100 mg/kg) treatment. All these outcomes implied that ACs exhibited AIP in a dose-dependent manner with maximal AIP imparted by artemisinin (100 mg/kg). This pre-clinical investigation avers the tremendous AIP of ACs targeting key molecular pathways. The current study divulges artemisinin as the most potent antiinflammatory agent among the tested compounds.